(untitled) (Jurnal Ilmu Pendidikan dan Kearifan Lokal, 2025)
This study aims to describe the scientific implementation in fiqh learning for students’ activeness and understanding, obstacles and solutions at MIN 21 Hulu Sungai Tengah. The implementation of this research applies a descriptive type using qualitative methods. The data obtained with qualitative techniques are the results of observations and interviews. Based on the data that has been found, this study will review the implementation of fiqh learning by implementing scientific activities for students’ activeness and understanding which are already going quite well, where the teacher applies let’s observe, ask, try, collect problems, associate, and communicate. Through the application of this scientific approach it can be concluded that it can influence the development of students’ skills including critical thinking, skilled in communicating, and skilled in collaboration and investigation. Obstacles were found in the scientific implementation of this learning process in the form of a lack of interest and asking students and the lack of utilization of existing facilities and infrastructure. The solution that can be done by the school is to seek educators to take part in training and teachers insert the use of learning media in certain materials